2011
DOI: 10.1055/s-0031-1284365
|View full text |Cite
|
Sign up to set email alerts
|

Paget’s Disease of Bone and Calcium Homeostasis: Focus on Bisphosphonate Treatment

Abstract: Paget's disease of bone (PDB) is the second most common metabolic bone disease. Bisphosphonates (BPs) are currently the drugs of choice for PDB. PDB and osteomalacia are both common in the elderly. The concept of relative vitamin D deficiency in patients with PDB was suggested long ago, but it has not yet elucidated. Both diseases predispose to fractures, but their combined action to fragility has not been studied yet. The older BPs, mainly etidronate, further inhibit bone mineralization. Mineralization defect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 40 publications
0
17
0
1
Order By: Relevance
“…Other preclinical studies and clinical observations have demonstrated that BPs, in particular alendronate and ZOL, delay or inhibit tooth eruption causing several dental abnormalities [14][15][16][17] and may, as in the juvenile Paget's disease of bone, exert an inhibitory effect on bone mineralization [18]. Such inhibition of mineralization has been observed for various BPs using calvaria osteoblast culture [19].…”
Section: Introductionmentioning
confidence: 89%
“…Other preclinical studies and clinical observations have demonstrated that BPs, in particular alendronate and ZOL, delay or inhibit tooth eruption causing several dental abnormalities [14][15][16][17] and may, as in the juvenile Paget's disease of bone, exert an inhibitory effect on bone mineralization [18]. Such inhibition of mineralization has been observed for various BPs using calvaria osteoblast culture [19].…”
Section: Introductionmentioning
confidence: 89%
“…Bone scintigraphy proved to be an effective valuable tool for evaluation of disease activity in the presence of pain in subjects with values of total alkaline phosphatase in the normal range. This review highlights areas of increased uptake and intense osteometabolic persist after infusion therapy suggesting the real need for re-treatment intravenous bisphosphonates (19). The potency of the drug was higher than assumed and does not require a subsequent annual infusion, as is shown in the technical form, while demonstrating the importance of reevaluate patients even after 1 year to monitor their levels of calcium, phosphate and PTH and continuing integrating daily calcium and Vit D.…”
Section: Discussionmentioning
confidence: 98%
“…Literatürde belirtildiği gibi, Paget hastalığında hipokalsemi ve ikincil hiperparatiroidizm sorun olarak karşımıza çıkmaktadır. Bu nedenle, tedaviden önce serum kalsiyum ve D vitamini düzeyi düzeltilmeli, tedaviden sonra normokalsemi sağlanıncaya dek kalsiyum, D vitamini desteğine devam edilmelidir (6).…”
Section: Discussionunclassified